DETERMINASI SOSIAL DAN GAYA HIDUP TERHADAP EPIDEMIOLOGI HIPERTENSI DI PROVINSI NTB: SEBUAH KAJIAN KESEHATAN MASYARAKAT - Darma Karno; Jaswadi, Jaswadi; Muh. Emilia Sa'id Rasyid; Lalu Iman Saptahadi; Baiq Reni Pratiwi; Yuly Peristiowati (Jurnal Cakrawala Ilmiah, 2025)
Objective: This article aims to analyze the social and lifestyle determinants that contribute to the epidemiology of hypertension in West Nusa Tenggara (NTB) Province. This study was conducted to understand how social, behavioral, and environmental factors influence the high incidence of hypertension, and how public health policies can be optimized for prevention and control. Methods: This study used a narrative literature review method by searching publications on Google Scholar, PubMed, ScienceDirect, and DOAJ, as well as official reports such as Riskesdas, the NTB Health Profile, and WHO reports. Keywords included "hypertension," "social determinants," "lifestyle risk factors," "Indonesia," and "NTB." The selected literature focused on hypertension prevalence, socioeconomic risk factors, consumption patterns, physical activity, stress, and environmental determinants. The analysis was conducted using a narrative synthesis based on the Social Determinants of Health (SDH) framework and theories of non-communicable disease epidemiology. Results: This study shows that hypertension in NTB is influenced by a combination of socioeconomic factors, lifestyle, and environmental conditions. The prevalence of hypertension in West Nusa Tenggara (NTB) among those aged 18 and above is increasing along with urbanization and changes in consumption patterns. Social factors such as low income, limited education, and residential environments that are less conducive to physical activity contribute to the risk of hypertension. In terms of lifestyle, excessive salt consumption, a diet high in fat and low in fruits and vegetables, smoking, lack of physical activity, and high levels of stress are the most dominant determinants. Basic Health Research (Riskesdas) data shows that districts/cities such as Mataram City, West Lombok, and East Lombok have a higher prevalence of hypertension than other regions, in line with changes in urban lifestyles and the rise in obesity. Implications: These findings emphasize the need for multisectoral interventions to control hypertension, including improving nutrition education, promoting physical activity, reducing salt consumption, and increasing access to screening services. Local governments need to integrate health policies with the education, social, and spatial planning sectors to create an environment that supports a healthy lifestyle. Limitations: This study relies on secondary data from various heterogeneous sources, which cannot quantitatively describe the strength of the relationship.